A semiotic analysis of the Qur’anic verses concerning aggression: semantic, rhetorical, and phonetic perspectives - Younis, Asmaa Wajeh (Journal of Arabic Language Sciences and Literature, 2025)
This study aims to examine the concept of aggression in the Qur’an from a semiotic perspective, by analyzing the phonetic, linguistic, and symbolic signs associated with it, and how the Qur’an employs rhetorical, phonetic, and semantic means to warn against transgressing legitimate boundaries. The research addresses the dimensions of aggression in the human relationship with God, with oneself, and with society, through a network of linguistic and symbolic signs that reveal the depth of the Qur’anic text’s semantic structure. Moreover, the study demonstrates how the Qur’anic semiotics of aggression establish an ethical and legislative system governing human behavior, clarifying the relationship between language, sound, and meaning in the discourse of the Qur’an.